PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF “RABAPRO” UNTUK MENINGKATKAN KEMAMPUAN LITERASI DIGITAL SISWA KELAS IV DI SEKOLAH DASAR - Widi Anugrah, Betha; Laila, Alfi; Alya Salsabila, Thalita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research focuses on creating engaging educational tools named “RABAPRO” (Diverse Environments and Occupations) to enhance the digital literacy abilities of fourth-grade students in elementary school. The investigation utilized the Research and Development (R&D) approach, specifically following the ADDIE framework, which comprises stages such as analysis, design, development, implementation, and assessment. The research took place at SDN Gayam 3, located in Kediri City, involving 20 fourth-grade pupils and one classroom teacher as study participants. Techniques for gathering data included conducting interviews, distributing questionnaires, obtaining expert evaluations, and administering pretest and posttest assessments. Findings from the research indicated that the RABAPRO interactive media was considered highly appropriate for educational purposes. Validation by media experts resulted in a score of 41 out of a total of 48, placing it in the very good range. On the other hand, validation from material experts scored 41 out of a possible 45, with an average feasibility rating of 2.73, also categorized as very good. The results of the implementation indicated that the media facilitated an increase in student engagement, motivation for learning, and comprehension of the topics related to different landscapes and professions. Furthermore, the outcomes from the effectiveness testing revealed that the data were normally distributed and homogeneous, with a significance level greater than 0.05. Therefore, RABAPRO interactive media is considered effective, practical, and appropriate for promoting digital literacy-based education in primary schools.